Diagnosis of bed agglomeration during biomass pyrolysis in fluidized-bed at a wide range of temperatures - Burton, A.; Wu, Hongwei (Elsevier Ltd, 2016)
This paper reports the diagnosis of bed agglomeration during biomass fast pyrolysis in a fluidized-bed reactor at a wide range of temperatures (200–700 °C). The results show that under all conditions, bed agglomeration can be modelled using sand loading (SL), which is the mass of sand that directly interacts with the incoming biomass feed normalised to the total mass of biomass fed into the reactor. The values of sand loading SL during pyrolysis is greatly influenced by the ethanol-soluble extractive contained within the raw biomass. For the pyrolysis of the raw biomass, at temperatures <310 °C, SL follows an endothermic reaction pathway (Ea = 28 kJ/mole) during which its values increases with increasing temperature. However, at higher temperatures >350 °C, SL follows an exothermic reaction pathway (Ea = –45 kJ/mole) during which its values decrease with increasing temperature.